Hybrid Biocomposites: Utilization in Aerospace Engineering - Kuram, Emel (Springer International Publishing, 2022)
Biocomposites have been developed by the researchers in recent years owing to rising pressure on the protection of the environment. Poor interface, moderate to lower mechanical properties, and moisture intake are some drawbacks of biocomposites for partial or full change with synthetic composites. To overcome these drawbacks, hybridizing, blending two or more reinforcements instead of single reinforcement in a polymeric matrix, is widely employed nowadays. Considerable increase has been observed in the utilization of biocomposites or hybrid biocomposites in the aerospace industry such as gas turbine engines (fan blade and cases) over the past decade for weight reduction. Therefore, in this chapter, the works about hybrid biocomposites and their applications in the aerospace industry (aircraft frames, engine construction, and interior cabin components) are reported. Also, this chapter aims to analyze the synergistic effect of hybrid biocomposites in the aerospace applications with a discussion of recent research in this area. © 2023 Elsevier B.V., All rights reserved.
Keywords: Aerospace applications; Hybrid biocomposites; Hybridization